Analysis The Impact of Service Quality, Customer Satisfaction, Customer Commitment, On Word of Mouth - Kevin Viadi (Bina Nusantara University, 2021)
The development of an Internet service influenced by the quality of services provided and customer satisfaction that have an impact on customers who are committed to continue to subscribe to the impact to the customer to do word of mouth. The purpose of this study was to determine the effect of service quality and customer satisfaction, for customer commitment and its impact on word of mouth that is useful to get a promotion without charge on the internet located around Jakarta. The method used in this study is path analysis by distributing questionnaires and then tested for normality, validity, and reliability as evidence that the data obtained feasible to do research. Analysis of the results achieved is the influence of service quality and customer satisfaction that have an impact on customer commitment that influence word of mouth. From data processing, the quality of service and customer satisfaction affects customer commitmentt. While the quality of service, customer commitment and customer commitment influence word of mouth.